Academic Chairpersons in Academic Medicine & Flexible Career Policies - Jean McLaughlin (Academic Chairpersons Conference Proceedings, 2015)
A 2012 survey of faculty in academic medicine collected information about their perceptions of climate and support for the use of flexible career policies and programs. The data were analyzed by gender, parental status, and having been a department chair. Recommendations for administrators in schools of medicine will be discussed.
Keywords: academic medicine; faculty career flexibility